Arylmalonate Decarboxylase—A Versatile Biocatalyst for the Synthesis of Optically Pure Carboxylic Acids - Schweiger, Anna K.; Miyamoto, Kenji; Kourist, Robert (Frontiers in Catalysis, 2021)
Bacterial arylmalonate decarboxylase (AMDase) is an intriguing cofactor-independent enzyme with a broad substrate spectrum. Particularly, the highly stereoselective transformation of diverse arylmalonic acids into the corresponding chiral α-arylpropionates has contributed to the broad recognition of this biocatalyst. While, more than 30 years after its discovery, the native substrate and function of AMDase still remain undiscovered, contributions from multiple fields have ever since brought forth a powerful collection of AMDase variants to access a wide variety of optically pure -substituted propionates. This review aims at providing a comprehensive overview of the development of AMDase from an enzyme with unknown function up to a powerful tailored biocatalyst for the synthesis of industrially relevant optically pure α-arylpropionates. Historical perspectives as well as recent achievements in the field will be covered within this work.